Sistem Optimasi Penjadwalan Mesin Produksi Menggunakan Metode GUPTA Berbasis Android - Mashuri, Chamdan; Mujianto, Ahmad Heru; Sucipto, Hadi; Arsam, Rinaldo Yudianto (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
Research has been carried out by developing an optimization information system for scheduling production machines by applying the Android-based GUPTA method. This android-based application is able to optimize production time, because in the android application it implements the GUPTA algorithm which uses the calculation of the comparative processing time on every machine in the company by prioritizing the smallest processing time for scheduling which aims to optimize production scheduling time, by paying attention to the value of makespan to produce product size 12 griddle, size 14 griddle, 16 size griddle, 18 size griddle and 20 size griddle so that an optimal makespan value is obtained. The GUPTA method can be used in problems with more than two machines, because this method combines the time of each process on the first and subsequent machines to find the minimum value and can only be used in pure flow shop scheduling. The advantage of this method is that it determines scheduling only on one machine group. This research resulted in an Android-based application that can schedule products to be produced by machines automatically. From the results of testing with a total of 12 pieces of production in each product with a total of 5 different sizes, the minimum value of makespan is obtained, namely 2054569 minutes with the sequence of product processing with work order 12 griddle, griddle 18, griddle 20, griddle 16, and griddle 14 The accuracy of the application test results shows 98.87% for the first time and 98.84% for the second time when compared with manual calculations.